Role of Ethics in Nature-Human Relationship: a Pragmatic Inquiry - Jena, Anita (Problemy Ekorozwoju, 2024)
Primitive people, in their initial struggle for existence, must have found Nature to be a formidable force to reckon with. Our ancestors eked out their means of survival from the abundant bounties of the ancient world with the meager tools at their disposal and sometimes tried to placate Nature by worshipping her. The earth was a rich mother and the needs of the early people were few. With time the ever increasing demands of humankind were matched by their growing power to wreak destruction and havoc. They destroyed forests and dug into the earth with unrestricted abandon in the quest of greater wealth and enjoyment, slaughtered every type of life for food and even for the mere pleasure of killing. Human beings remain the only predator that kills the young adults of a species, damaging the reproductive capital of the latter. Philosophers have argued against the wanton destruction of the earth’s resources. That these warnings have been largely ignored is apparent in the danger signs that have started to raise a question mark on the future of life on this planet. Therefore, these ethical theories are needed to be analyzing in a pragmatic point of view of their applications. The tendency of the theories is to concentrate on the former and take the latter for granted. This creates a gap between knowledge and application of environmental ethics. There must be some aspects other than worldviews that affects human behavior. We proceed with a pragmatic theory of ethics which takes into account the practical aspects and strengthen it further with a psychological probe into the aspects responsible for creating the gap.